Some Peculiarities of Jet Flows in a Deflecting Stream - Epstein, A.; Hendrikson, V. (Engineering Transactions, 1974)
Results of experimental study of turbulent nonbuoyant and buoyant jets issuing into the cross-stream are presented. It has been shown that the flow has different patterns depending on initial ratios of jet to stream momentum and of jet buoyancy to stream momentum. For given ratios different types of temperature distributions were observed at distances near the orifice and far downstream with tendency to similarity at each stage.